Le immagini del potere. La Deutsche Kunstgesellschaft e l’arte del Terzo Reich (Studia theodisca, 2011)
This essay deals with the uses of art for representing power in Germany from the Weimar Republic to the Second World War. It focuses on the figure of Bettina Feistel-Rohmeder and the origins of her Deutsche Kunstgesellschaft. A brief comparison of the art promoted by the German Art Society with the one later made official by Hitler’s regime will demonstrate their common roots in the völkisch (nationalistic) milieu and the romantic tradition. This essay also presents a selection of a few articles collected in “Das Bild”.